Head and neck pleomorphic myxoid liposarcoma in a child with Li-Fraumeni syndrome. (August 2019) - Francom, Christian R.; Leoniak, Steven M.; Lovell, Mark A.; Herrmann, Brian W.
Abstract: Introduction: Pleomorphic myxoid liposarcoma is a rare and aggressive cancer seen in the pediatric population that has been previously associated with hereditable cancer disorders like Li Fraumeni syndrome. We present a case report and review of the relevant literature. Case presentation: Pleomorphic myxoid liposarcoma presenting as a second primary tumor in a child with a strong family history for cancer led to diagnosis of Li-Fraumeni syndrome, which is associated with TP53 tumor suppressor gene inactivation. Management and outcome: The tumor was fully excised, but postoperative radiation was deferred to limit future radiation-induced tumorgenesis. Discussion: Pleomorphic myxoid liposarcoma is rare but aggressive, and should prompt caregivers to test for potential hereditable cancer disorders. Li-Fraumeni syndrome is associated with early onset neoplasia and development of recurrent primary tumors. Its presence affects treatment decisions and methods of surveillance. Chemoradiation should be used judiciously in this population.